Implementation of character education through the development of relegius and moral values - Aisiyah Aisiyah (JURNAL SOCIUS, 2022)
The purpose of this study was to see how the efforts of character education and religious and moral values in early childhood. The research method used in this research is qualitative. The data sources used in this study were obtained from informants who were selected using a purposive technique. Data analysis is done inductively starting from empirical facts and then deduced with theory. The results found in this study 1. The approach used in Khadijah Islamic Kindergarten Plus is the Development approach through the singing method, storytelling method, question and answer method, and the domesrasi method. While at Kindergarten Isalm Al-Ikhwan the development approach is through the habituation method, the storytelling method, the demonstration method, the question and answer method, and the singing method. 2. Development of valuesand morals in T Islam Khadijah by singing religious songs. From the results of this study, it is clear that there are many ways to implement character education in early childhood, but it is possible that it can also be applied to elementary, middle and high school children